Interpretasi Karakteristik Dewa Siwa Sebagai Inspirasi Seni Lukis - Sadewa, Kadek Ian Gangga; Adnyana, I Wayan; Yudha, I Made Bendi (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This thesis contains a description of the creation of painting with the theme "Interpretation of the Characteristics ofLord Shiva as the Inspiration for Painting". The discussion of this theme is based on the symbolic form of Lord Shiva who has a background story and deep spiritual meaning, feels very relevant to be implemented regarding thephenomenon of social life in the modern era like today. The results are manifested in paintings using the creationmethod of Graham Wallas. The creation method includes the stages of preparation, incubation, getting inspiration, totesting. At the preparation stage, knowledge, insight, and framework of thinking are processed as instruments in findingproblems and solving problems, including the preparation of mind mapping. Towards the incubation stage, thesubconscious/preconscious takes over the process of searching and solving problems. At the stage of getting inspiration, the conscious and logic take back control to be able to elaborate on data or even ideas obtained previously to then beformulated as a concept. This stage is carried out by making a sketch as a record of the idea so that it is not biased andspread everywhere. The last is the testing stage which is carried out simultaneously with the formation or manifestationof the work. The results of this research and creation are in the form of six paintings about the characteristics of LordShiva with the titles (1) Shiva Nilakantha, (2) Shiva Trinetra, (3) Shiva Nataraja, (4) Lingga Yoni, (5) Trisula, (6) Nandhi. The meaning of the characteristics of Lord Shiva is poured into metaphorical visual symbols, with relevantassumptions, so as to achieve a narrative that is intended to be conveyed. The concept of the painting is adjusted to thestyle of surrealism and symbolism, namely the expression of concepts through forms that go beyond reality, and byusing symbols as its strength.